Characterisation and Intercellular Mechanistic Analysis of Supramolecular, Cationic, mRNA-Loaded Polyplexes for Efficient Transfection in HEK293T and A549 Cells - Smith, Silvia (2023)
Part A: The approval of two mRNA vaccines for COVID-19 by the U.S. FDA generated significant attention from the scientific community for RNA technology, with its safety, efficacy, and rapid production capabilities. Beyond infectious disease, RNA therapeutics hold great promise in cancer treatment and various other diseases. However, the physiochemical properties of free mRNA present significant challenges in achieving efficient intracellular delivery in vivo. Therefore, the development of effective delivery systems for exogenous RNA is crucial. Among various delivery methods, lipid and polymer-based nanoparticles (LNPs and PNPs) have emerged as prominent candidates. This review discusses different classes of PNPs, providing a comprehensive analysis of their molecular design criteria and plausible internalisation pathways within cells. Despite their favourable pharmacokinetics, precise tunability of chemical properties, and potential for cellular targeting, PNPs are behind LNPs in clinical advancement. This review explores the key challenges encountered in PNP development, with a particular emphasis on the importance of understanding PNP endosome escape mechanisms, which currently represent a bottleneck for improving transfection efficiency. By identifying how PNP composition, shape, and size influence endosome escape, PNP formulations can be optimised to deliver RNA therapeutics effectively and safely. Future perspectives and research directions necessary for the clinical translation of PNPs are also discussed.